Army of Shadows : Palestinian Collaboration with Zionism, 1917-1948 - Cohen, Hillel (Book collections on Project MUSE., 2008)
Inspired by stories he heard in the West Bank as a child, Cohen uncovers a hidden history, a history central to the narrative of the Israel-Palestine conflict. He tells the story of Arabs who from the very beginning of the conflict, sided with the Zionists and aided them politically, economically, and in security matters.